Malaria - Cut Titien Mauliza; Yenni Sulisma (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Malaria is one of the leading cause of illness and death worldwide. The prevalence of malaria cases in Indonesia in 2024 reached 543,965 positive cases and 34 deaths. Malaria is an infectious disease caused by parasites (protozoa) of the genus Plasmodium, which can be transmitted through the bite of Anopheles mosquitoes. Malaria is classified as a re-emerging disease, which refers to diseases that resurface due to natural phenomena, including environmental factors such as climate, temperature, and rainfall. The most effective way to prevent and control malaria is by breaking the transmission chain. Additionally, simple preventive measures that everyone in the community can take include avoiding or reducing mosquito bites, avoiding outdoor activities at night, sleeping under a mosquito net, applying mosquito repellent, installing screens on windows, cleaning mosquito breeding sites, and clearing bushes or dense vegetation around the house. In addressing clinical issues, medications can be used to prevent and stop clinical attacks.